Effect of peripheral blood lymphocyte count on the efficacy of immunotherapy combined with TKI in the treatment of advanced liver cancer - Zhao, Qian; Wang, Lei; Fu, Huilan; Zhang, Yuqin; Xie, Qiankun (Frontiers in Immunology, 2024)
Background & Aims: Compared with tyrosine kinase inhibitor (TKI) monotherapy, TKI combined with PD1 can improve the therapeutic effect of liver cancer and has been widely used in clinical practice. However, there is a lack of effective biomarkers to identify patients who would benefit more from this combination therapy. Therefore, this study aimed to evaluate whether baseline lymphocyte counts can identify patients with liver cancer who would benefit from targeted immune combination therapy.Methods: Data from patients with hepatocellular carcinoma (HCC) who received TKIs or TKIs in combination with PD1 between June 2018 and June 2020 were retrospectively collected. The patients were divided into high and low groups based on the median absolute count of peripheral lymphocytes before systemic therapy and differences in overall survival (OS) and progression-free survival (PFS) between TKI and TKI+PD1 were compared between the two groups.Results: In total, 72 patients were included in this study, with a median follow-up of 30 months. Both PFS and OS in the TKI+PD1 group showed a good prognostic trend (p = 0.058 and p = 0.077, respectively). Subgroup analyses based on peripheral blood lymphocyte counts showed that the combination regimen had a significant OS and PFS advantage only in patients with high peripheral blood lymphocyte counts (p = 0.036 and p = 0.031, respectively), but not in patients with low absolute peripheral blood lymphocyte counts (p = 0.819 and p = 0.913, respectively).Peripheral blood lymphocyte count is a simple and effective biomarker that can be used to identify patients with liver cancer who will benefit more from TKI+PD-1 combination therapy.